Ultrasonic enzymatic mediated extraction of eurycoma longifolia (tongkat ali) for cosmeceutical and nutraceutical applications - Elfira, Anuar (2014)
This thesis reported ultrasonic enzymatic mediated extraction of Eurycoma longifolia (Tongkat Ali) for cosmeceutical and nutraceutical applications. E. longifolia has been used for quite a long time by practitioners for medical use in Malaysia. Interest in its commercial value began when it is noted to have an aphrodisiac property for men. The use of active compounds in E. longifolia for various industries signifies the need of the most appropriate and standard method to extract it. Previously, several researchers have studied new extraction technique of E. longifolia. However, it has not been reported yet the ideal technique to optimize the extraction of active compounds in E. longifolia. This study is focused on hydrodistillation, enzymatic extraction, and ultrasonic enzymatic mediated extraction techniques in order to investigate the performance of each extraction technique. Comparison of HPLC chromatogram was made between the standard and sample of E. longifolia extract to determine the concentration for eurycomanone in each sample. The findings of the results show that the yield for hydrodistillation technique increased gradually until the 6 hours and declined afterward due to loss of some heat-sensitive bioactive compounds. This technique reported a total of 12.56% of yield for 12 hours of extraction process. Result obtained for the enzymatic extraction shows that the enzyme treatment enhanced the yield by nearly 2.1-fold relative to hydrodistillation technique. By applying the ultrasonic of 10% and 20% duty cycle on the enzyme-treated samples, the overall yield improved by nearly 2.4-fold and 2.6-fold respectively compared to hydrodistillation technique and 1.2-fold and 1.1-fold respectively compared to enzymatic extraction technique. Thus, as a conclusion, apart from being effective, the ultrasonic enzymatic mediated extraction of E. longifolia is the best extraction technique to improve the extracted productivity and shorten the extraction time which in turn may be beneficial to commercialization of Eurycoma longifolia for cosmeceutical and nutraceutical application in the future